Perjanjian Pengikatan Jual Beli Hak Atas Tanah Sebagai Jaminan Kredit Hak Tanggungan - Jennis Kristina (Darma Cendika Catholic University, 2019)
Bank credit activities carried out with all internal policies must apply the principle of prudence. PPJB which is a binding agreement between the parties whose rights are not yet perfect, compilation is used as a guarantee of mortgage rights can be a cause of failure to fulfill the prudential principle. This research is a normative juridical research, using literature approach. The results of the discussion and conclusion of this study show: Bank's internal policy that states PPJB used as security of mortgage can be done using the process of making a Note Cover. This can bring the bank in the position of being stolen because making a Cover Note does not require an approved deed related to the buying and selling process such as a sale and purchase certificate or certificate. Furthermore, debtors who are negligent or have no good intentions, the Cover Note does not increase to become a certificate. Such participation makes the object to be requested or bound with mortgage rights still needed, so the position of the bank's creditors is threatened as concurrent creditors who do not have a special position of compilation in the credit process.